In vitro and in vivo Inhibitory Activity of NADPH Against the AmpC BER Class C β-Lactamase - Na, Jung-Hyun; Lee, Tae Hee; Park, Soo-Bong; Kim, Min-Kyu; Jeong, Bo-Gyeong; Chung, Kyung Min; Cha, Sun-Shin (Frontiers in Cellular and Infection Microbiology, 2018)
β-Lactamase-mediated resistance to β-lactam antibiotics has been significantly threatening the efficacy of these clinically important antibacterial drugs. Although some β-lactamase inhibitors are prescribed in combination with β-lactam antibiotics to overcome this resistance, the emergence of enzymes resistant to current inhibitors necessitates the development of novel β-lactamase inhibitors. In this study, we evaluated the inhibitory effect of dinucleotides on an extended-spectrum class C β-lactamase, AmpC BER. Of the dinucleotides tested, NADPH, a cellular metabolite, decreased the nitrocefin-hydrolyzing activity of the enzyme with a Ki value of 103 μM in a non-covalent competitive manner. In addition, the dissociation constant (KD) between AmpC BER and NADPH was measured to be 40 μM. According to our in vitro susceptibility study based on growth curves, NADPH restored the antibacterial activity of ceftazidime against a ceftazidime-resistant Escherichia coli BER strain producing AmpC BER. Remarkably, a single dose of combinatory treatment with NADPH and ceftazidime conferred marked therapeutic efficacy (100% survival rate) in a mouse model infected by the E. coli BER strain although NADPH or ceftazidime alone failed to prevent the lethal bacterial infection. These results may offer the potential of the dinucleotide scaffold for the development of novel β-lactamase inhibitors.